A sociologia e a literatura: ampliando o pensamento sociológico através de sequência didática - Batista, Melanilce Karla da Silva (2024)
This work aims to present a didactic sequence, carried out as a research product for the Professional Master's Degree in Teaching Sociology in the research line Youth and contemporary themes with an emphasis on the teaching of Sociology. Sociology has many relevant themes and its importance is consolidated in the formation of a young person who is critical and aware of reality. Considering this situation, the reading habits of young people who attend EEEP Mário Alencar are observed. For the analysis, an intervention project was carried out, instrumentalized from the construction of a didactic sequence, using as inspiration the teaching methodology referenced in historical-critical pedagogy, designed by professor João Luiz Gasparin, prioritizing dialogues and reflections on the contents studied in classroom, with the reading of the short story The Lottery by Shirley Jackson and the implementation of a school literary project, Ciranda de Leitura, where the main objective is to use literature as a tool for teaching Sociology. The classes were planned for the first and second year classes of high school at EEEP Mário Alencar, taking into account the availability of schedules and daily activities, as well as the attitudes of young people in relation to reading the book 'O Auto da Compadecida' by Ariano Suassuna, who was our object of analysis. The pedagogical intervention was carried out during class hours, in the format of conversation circles, which enabled greater interaction between the students and the teacher.